Antimicrobial Activity of the Volatile Oil from the Leaves of Piper betle Linn. - Caburian, Adeltrudes B.; Osi, Marina O.; Belardo, Reiner E. (Silliman Journal, 2022)
The study was carried out with the objective of evaluating the antibacterial and antifungal potentials and non-mutagenic activity of the pure volatile oil from the leaves of Piper betle vine, a traditional antimicrobial medicine. It was also the purpose of the study to determine the physicochemical properties and composition of the pure oil. The determined physical constants were congealing temperature (-4o C), melting point (8°C), specific gravity (0.9313), optical activity (+4.2307), = and refractive index (1.4525). Twenty oil components were identified by gas chromatography-mass spectroscopy (GC-MS) analysis – among them are: 5-(2-propenyl)-1,3-benzodioxole, eugenol isomers, 3-carene and caryophyllene. In this study, the microbial activity of the pure oil from the leaves of P. betle was evaluated for potential antimicrobial activity using agar-well diffusion method. The antibacterial activity of the oil at 100μg/mL concentration were tested against Staphylococcus aureus, Escherichia coli and Bacillus subtilis while 20μg/mL, 30μg/mL and 40μg/ ml concentrations of the oil were used against Streptococcus pyogenes. The antifungal activity of the oil at 100μg/mL was tested against Candida albicans and 2μg/mL, 10μg/mL and 15μg/mL concentrations against Trichophyton mentagrophytes. Zone of inhibition of the pure oil was compared with standards mupirocin for antibacterial activity and clotrimazole for antifungal activity. The results show active to very active inhibition of the bacterial and fungal growth against the test organisms. The antimicrobial action of the P. betle oil is due to bioactive constituents such as isosaffrol, eugenol and caryophyllene among others which are well known for their antibacterial and antifungal properties. P. betle oil does not possess carcinogenic and/or mutagenic activity as evident of lower number of micronucleus formed in rat bone marrow cells after treatment of the pure oil when compared to cyclophosphamide. The mechanism of its antimicrobial activity is not yet well understood. Further studies on the pathway of microbial growth inhibition are recommended and preformulation data obtained in this study should be validated to establish specifications of the oil.